The Nuclear Age in Popular Media A Transnational History, 1945–1965 - Lente, Dick van.; Lente, Dick van. (Palgrave Studies in the History of Science and Technology, 2012)
The atomic age was described as one that might soon end in the destruction of human civilization, but from the beginning, utopian images were attached to it as well. This book compares representations of nuclear power in popular media from around the world to to trace divergences, convergences, and exchanges.